From visuo-motor interactions to imitation learning: Behavioural and brain imaging studies - Vogt, S.; Tomaschke, R. (Journal of Sports Sciences, 2007)
We review three areas of research and theory relating to the involvement of motor processing in action observation: behavioural studies on imitation learning, behavioural work on short-term visuomotor interactions, and related neurophysiological and neuroimaging work. A large number of behavioural studies now indicate bi-directional links between perception and action: visual processing can automatically induce related motor processes, and motor actions can direct future visual processing. The related concept of direct matching (Rizzolatti et al., 2001) does not, however, imply that observed actions are transduced into a corresponding motor representation that would guarantee an instant and accurate imitation. Rather, studies on the mirror neuron system indicate that action observation engages the observer's own motor prototype of the observed action. This allows for enhanced action recognition, imitation recognition, and, predominantly in humans, imitation and observational learning. Despite the clear impact of action observation on motor representations, recent neuroimaging work also indicates the overlap of imitation learning with processes of non-imitative skill acquisition.